Cell Shape Impacts on the Positioning of the Mitotic Spindle with Respect to the Substratum - Ispolatov, y (American Society for Cell Biology, 2015)
All known mechanisms of mitotic spindle orientation rely on astral microtubules. We report that even in the absence of astral microtubules, metaphase spindles in MDCK and HeLa cells are not randomly positioned along their x-z dimension, but preferentially adopt shallow β angles between spindle pole axis and substratum. The nonrandom spindle positioning is due to constraints imposed by the cell cortex in flat cells that drive spindles that are longer and/or wider than the cell s height into a tilted, quasidiagonal x-z position. In rounder cells, which are taller, fewer cortical constraints make the x-z spindle position more random. Reestablishment of astral microtubule-mediated forces align the spindle poles with cortical cues parallel to the substratum in all cells. However, in flat cells, they frequently cause spindle deformations. Similar deformations are apparent when confined spindles rotate from tilted to parallel positions while MDCK cells progress from prometaphase to metaphase. The spindle disruptions cause the engagement of the spindle assembly checkpoint. We propose that cell rounding serves to maintain spindle integrity during its positioning. © 2015 Lázaro-Diéguez et al.